INTERNALIZATION OF RELIGIOUS MODERATION THROUGH DIGITAL PREACHING A Critical Discourse Analysis of Ustadz Adi Hidayat’s Lectures on YouTube - Afdhalia, Afifah Nabila; Habibi, Faisol; Kuswanjono, Arqom (Universitas Islam Indonesia, 2025)
Religious moderation emphasizes tolerant, inclusive, and fair attitudes amidst religious, cultural, and traditional diversity. This study analyzes Ustadz Adi Hidayat's (UAH) YouTube lectures using Critical Discourse Analysis (CDA), focusing on text, social cognition, and social context, to examine how he constructs and conveys religious moderation, aligning with Indonesia's diverse social landscape. The analysis reveals UAH discursively presents moderation as a practical solution for harmony, not just a theological concept. His discourse employs rhetorical strategies, like the stories of Fathu Makkah and the Treaty of Hudaibiyah, to underscore compassion, forgiveness, and harmony as core tenets. UAH's lectures implicitly guide audiences to understand moderation as an intrinsic part of Islamic teachings, promoting balance and rejecting extremism. Grounded in religious proofs (dalil) and historical narratives, his approach counters disinformation and polarization by encouraging a balanced religious understanding. This discourse significantly strengthens social harmony in Indonesia by cultivating tolerant, inclusive, and just attitudes among his vast digital audience. This research confirms UAH's discourse on religious moderation is highly relevant for both local cohesion and global peace.